Kreativitas Mahasiswa Pada Mata Kuliah Desain Ragam Hias Di Jurusan Kesejahteraan Keluarga Fakultas Teknik Universitas Negeri Padang - Novika, Vera Samsu; Katin, Yusmar Emmy; Rahmiati, Rahmiati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
This research is a descritive quantitave research. Research population are students on subject of design variety of decoration in the field of family welfare periode Januari to June 2013, the number of population are 37 students. Sampling technic is total technical sampling. Data collected by using questionairs likert scale. Tested questionnaire to students in the incoming year 2012 which took a course design ornament by 30 people. To determine logical validity of the instrument in order to be able to know instrument reliability with alpha cronbach formula. Reliability analysis shows that the reliability of questionare is in a very strong group, the data is analysed by technical percentage. Research result shows that in general students creativity is categorized in 4 sub indicators is indicators openness to new experience is in middle category 68,9%, indicators freedom to self express in middle category 66,3%, indicators appreciate fantasy is in middle category 65,5%, indicators respect to idea in middle category 65,0%. Based on score variable distribution in field of decoration variety, it is found not students creativity in the middle category, achievment of questioner analysis in the middle category 66,9%. To sum up that students creativity on subject of design variety of decoration in the field of family welfare faculty of technic state university of padang is middle category. Â Â Hint: Students Creativity, Subject Design Variety of Decoration